Paediatric drug development of ramipril: reformulation, in vitro and in vivo evaluation. (21st October 2015) - Russell, Craig; Begum, Sumyra; Hussain, Yasar; Hussain, Majad; Huen, David; Rahman, Ayesha S.; Perrie, Yvonne; Mohammed, Afzal R.
Abstract: Ramipril is used mainly for the treatment of hypertension and to reduce incidence of fatality following heart attacks in patients who develop indications of congestive heart failure. In the paediatric population, it is used most commonly for the treatment of heart failure, hypertension in type 1 diabetes and diabetic nephropathy. Due to the lack of a suitable liquid formulation, the current study evaluates the development of a range of oral liquid formulations of ramipril along with their in vitro and in vivo absorption studies. Three different formulation development approaches were studied: solubilisation using acetic acid as a co-solvent, complexation with hydroxypropyl-β-cyclodextrin (HP-β-CD) and suspension development using xanthan gum. Systematic optimisation of formulation parameters for the different strategies resulted in the development of products stable for 12 months at long-term stability conditions. In vivo evaluation showed C max of 10.48 µg/ml for co-solvent, 13.04 µg/ml for the suspension and 29.58 µg/ml for the cyclodextrin-based ramipril solution. Interestingly, both ramipril solution (co-solvent) and the suspension showed a T max of 2.5 h, however, cyclodextrin-based ramipril produced T max at 0.75 h following administration. The results presented in this study provide translatable products for oral liquid ramipril which offer preferential paediatric use over existing alternatives.